EXPERIMENTAL STUDY OF THE FREQUENCY CHARACTERISTICS OF AN ELECTROPNEUMATIC TRACKING SYSTEM WITH HIGH SPEED PNEUMATIC VALVES AND PWM CONTROL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper describes an experimental study on the frequency characteristics of an electropneumatic tracking system with a high-speed pneumatic on/off valve (HSPV) and Pulse Width Modulation (PWM) control. A demonstration experimental test bench has been developed to analyze the Bode diagrams of magnitude and phase for an electropneumatic tracking system with a double-rod pneumatic cylinder, and the system's critical frequency has been determined. A specialized virtual instrument is used for control and data acquisition. The process control and data processing are performed automatically by a computer and the corresponding NI interface board. The results are presented in graphical form and analysis of the obtained Bode Diagrams was made.